The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1542/peds.2008-1316
|View full text |Cite
|
Sign up to set email alerts
|

CD4 Counts Decline Despite Nutritional Recovery in HIV-Infected Zambian Children With Severe Malnutrition

Abstract: Severe malnutrition did not reduce the CD4 counts of children without HIV. HIV-infected children with severe malnutrition may respond well to nutritional rehabilitation, despite low CD4 counts, but nearly all require early antiretroviral therapy to prevent disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 24 publications
3
31
0
Order By: Relevance
“…The majority (54%) of children with HIV in this study presented with oedema, consistent with reports of oedema in 67% and 71% from Malawi (6,18) and 50% in Zambia (17), though rates were lower in Burkina Faso and Uganda at 37-43% (13,21,34).…”
Section: Anthropometrysupporting
confidence: 89%
See 1 more Smart Citation
“…The majority (54%) of children with HIV in this study presented with oedema, consistent with reports of oedema in 67% and 71% from Malawi (6,18) and 50% in Zambia (17), though rates were lower in Burkina Faso and Uganda at 37-43% (13,21,34).…”
Section: Anthropometrysupporting
confidence: 89%
“…Nutritional features which may help identify underling HIV in a child with SAM include wasting (marasmus), reported to be 4-6 times more common in HIV infection (3,13,(15)(16)(17)(18)(19)(20), and a weight <60% of the expected median for age (18).…”
Section: Introductionmentioning
confidence: 99%
“…This is contrary to our study participants who were at an early stage of infection It is known that HIV has a close relationship with nutritional status. However, it's impact on BMI is independent of the CD4 count [26,34]. This assumption was confirmed in our study by the absence of correlation between BMI after 6 months and baseline CD4.…”
Section: Discussionsupporting
confidence: 84%
“…Other investigators have made similar observations with HIV patients having rates of overweight/obesity as high as that of the general population [23,25]. Previously overweight/obesity in HIV/AIDS was associated with HAARTS intake [8,26]. Recent evidence exists that HAARTS represents just a modest contribution to weight gain in HIV patients and that many HIV patients are already overweight/ obese before HAARTS initiation [11].…”
Section: Discussionmentioning
confidence: 70%
“…However, in our experience, HIV-infected ART-naive children with SAM who are hospitalized and receive nutritional rehabilitation tend to have a slower weight gain than do HIVnegative children. A study from Zambia showed that infected children with SAM remain severely immunosuppressed after recovery from SAM (18). It is important to document the effect of ART on the nutritional and immune recovery in HIV-infected children with SAM during nutritional rehabilitation.…”
Section: Introductionmentioning
confidence: 99%